The Role of Cuttings in Silki Breeding (Eurasian Scientific Herald, 2023)
The article studies the planting of fodder plantings of the bush type, laid by cuttings in a permanent place - very promising. Such plantings are characterized by a short till exploitation period and high leaf yield: in the first year after planting the cuttings, 3-4 tons of leaves are obtained from 1 ha, after two - 12-14 tons